Human biomonitoring of mycotoxins under HBM4EU: update on key outputs - Alvito, Paula (2022)
The European Human Biomonitoring Initiative (HBM4EU) is a project gathering 30 countries, funded under Horizon 2020 and running from 2017 until 2021. The goal of HBM4EU is to generate evidence on the current exposure of European citizens to chemicals and on their possible health effects to assess the associated risks. Following a systematic prioritization exercise, the mycotoxins Deoxynivalenol (DON) and Fumonisin B1 (FB1) were considered as priority substances around which the HBM4EU research programme was developed. As part of the HBM4EU project, several policy questions are being addressed for these mycotoxins, concerning analytical methods, exposure levels and high exposure population groups in Europe (including workers), associated time trends, risk characterization, exposure models and toxicokinetic data, human biomonitoring guidance values, key events that determine the health effects of the target mycotoxins, effect biomarkers, data gaps and research needs. Key outputs from HBM4EU achieved until now for DON and FB1, include: i) a biomarker selected to assess human exposure to DON (total urinary DON) that will be used in the aligned studies, ii) several European laboratories selected to perform DON analysis after passing an interlaboratory study, ii) a research protocol on human exposure and geographic variations in Europe, iv) a risk assessment plan to assess DON and FB1 exposure in Europe, v) a review of available toxicokinetics models, vi) a draft on the possible mechanisms of FB1-induced adverse health effects and vii) a specific effect biomarker for FB1.